Pengaruh tingkat pendidikan, sikap kerja dan keterampilan kerja terhadap prestasi kerja karyawan pt. wahana sumber lestari samarinda - Kusma Maringan; Yonathan Pongtuluran; Siti Maria (AKUNTABEL, 2016)
The Effect of Education, Work Attitude, and Job Skills to Job Performance Employe PT. Wahana Sumber Lestari Samarinda (Supervised by Mr. Jonathan Pongtuluran and Mrs Siti Maria). The purpose of the study is to know the influence the Effect of Education, Work Attitude, and Job Skills to Job Performance. This research in PT. Wahana Sumber Lestari Samarinda. The sampling method by using sampling sensus, sampel that collect as much as 150 employe. Data in the research this use primary data that is interview and questionnaire. hypothesis testing used in this research is multiple linear regression using SPSS Versi 20. The results of this study show: 1) Level Education positive and significant effect to Job Performance PT. Wahana Sumber Lestari Samarinda, 2) Work Attitude positive and significant effect to Job Performance PT. Wahana Sumber Lestari Samarinda, 3)job  Skills  positive  and  significant  effect  to  Job  Performance  PT.  Wahana  Sumber  Lestari Samarinda.Keyword: Education level, Work attitude, Job Skills and Job Performance.